2017
DOI: 10.15252/embr.201744524
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic stress regulates ERK activity by controlling KSR‐RAF heterodimerization

Abstract: Altered cell metabolism is a hallmark of cancer, and targeting specific metabolic nodes is considered an attractive strategy for cancer therapy. In this study, we evaluate the effects of metabolic stressors on the deregulated ERK pathway in melanoma cells bearing activating mutations of the or oncogenes. We report that metabolic stressors promote the dimerization of KSR proteins with CRAF in NRAS-mutant cells, and with oncogenic BRAF in BRAF-mutant cells, thereby enhancing ERK pathway activation. Despite this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 59 publications
(79 reference statements)
1
14
2
Order By: Relevance
“…It is well established that the hetero-/homo-dimerization of RAF/KSR family kinases plays a determinant role in the activation of MAPK signaling, which requires the association of 14-3-3, a dimeric scaffold protein with their carboxyl-terminus [ 228 , 229 ]. Mechanistic studies have revealed that a 14-3-3 dimer associates with the C-terminus of two individual RAF/KSR molecules and facilitates their dimerization and subsequent activation [ 25 , 230 , 231 ] (Fig. 4 a).…”
Section: The Crosstalk Between Mapk and Ampk Signalingsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that the hetero-/homo-dimerization of RAF/KSR family kinases plays a determinant role in the activation of MAPK signaling, which requires the association of 14-3-3, a dimeric scaffold protein with their carboxyl-terminus [ 228 , 229 ]. Mechanistic studies have revealed that a 14-3-3 dimer associates with the C-terminus of two individual RAF/KSR molecules and facilitates their dimerization and subsequent activation [ 25 , 230 , 231 ] (Fig. 4 a).…”
Section: The Crosstalk Between Mapk and Ampk Signalingsmentioning
confidence: 99%
“…This molecular mechanism may also be responsible for the hyperactive MAPK signaling induced by metabolic stress in Ras-mutated melanoma. Upon metabolic perturbations, AMPK is activated in this type of melanoma cells and promotes KSR/CRAF heterodimerization likely through altering 14-3-3 binding manners, which leads to a highly activated MAPK signaling [ 230 ]. Besides CRAF and KSR, the association of BRAF with 14-3-3 is also regulated by AMPK-mediated phosphorylation.…”
Section: The Crosstalk Between Mapk and Ampk Signalingsmentioning
confidence: 99%
“…Melanoma cells (A375) were seeded at 10 cm plate, washed once with ice-cold phosphate-buffered saline (PBS), scraped out, and lysed as previously described [ 82 , 83 ]. The lysate was centrifugated at 13,000× g for 25 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Protein G Sepharose 4 Fast Flow beads (GE Healthcare, Chicago, IL, USA) were added and incubated for another 2–3 h at 4 °C on a slow rotator. Beads–immune complexes were washed as previously described [ 82 , 83 ]. The kinase assay was performed in the presence of 20 µM ATP and 500 ng of a recombinant human inactive MEK-1 as the substrate (Life Technologies, Prague, Czech Republic).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation